Effects of nutrition education sessions related to dietary iron on the dietary iron intake of high school wrestlers - Loprinzi, Marcella (My University, 1987)
This study compared the iron intake of high school wrestlers before and after the participation in three nutrition education sessions relating to dietary iron. The nutrition education sessions consisted of "The Basic Food Groups", "What is Iron Deficiency?", "How Iron Deficiency Affects Wrestling Performance" , "Sources of Foods High in Iron", "Methods of Prevention of Iron Deficiency", "How to Increase Iron in the Diet", "Label reading for Iron Determination", "How Iron is Lost from the Body", "Signs and Symptoms of Iron Deficiency", "Vitamin Supplements", and "Assertiveness". All education sessions included supplemental handouts pertaining to topics presented. The iron intake was measured by a three day dietary recall on food record sheets by the Ss before and after the education sessions. The results were measured on the Nutrition Data Base Computer System. The Ss consisted of 24 Logan High School and Aquinas High School wrestlers of La Crosse, Wisconsin. The subjects ranged in ages from 14 through 18. A t-test for two dependent groups was used to analyze the iron content results. There was a significant difference (p < .01) between the iron content of the Ss of the experimental group before and after exposure to nutrition education sessions relating to dietary iron. There was no significant change (p >.01) in the iron content of the control group. It was concluded that nutrition education sessions relating to dietary iron could have a positive effect on the dietary iron intake of high school wrestlers.
Keywords: Wrestlers; Iron -- Nutritional aspects; Nutrition -- Study and teaching -- United States